Talqin untuk Mahathir - Mohd. Sayuti Omar, 1960- (Kuala Lumpur : Tinta Merah, 1998)
On the leadership of Mahathir bin Mohamad, Malaysia's prime minister.
In Malay.
Keywords: Mahathir bin Mohamad, -- 1925-; Malaysia -- Politics and government